2012
DOI: 10.1111/pan.12022
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of success rate of ultrasound‐guided sciatic and femoral nerve block and neurostimulation in children with arthrogryposis multiplex congenita: a randomized clinical trial

Abstract: Ultrasonography significantly increases the success rate of sciatic and femoral block in arthrogryposis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 7 publications
0
21
0
1
Order By: Relevance
“…The duration to first analgesia is significantly higher with ultrasound-guided sciatic and femoral nerve blocks compared with nerve stimulation (8.6 ± 0.66 vs 7.6 ± 0.57 hours; P < 0.001), 9 but there was no difference in infraclavicular brachial plexus blocks when the 2 techniques were compared. 10 Time to first analgesia was longer with ultrasound-guided TAP block compared with no block (14.1 ± 4.9 hours vs 1.3 ± 1.1 hours; P < 0.05), 5 ultrasound-guided TAP block compared with wound infiltration (17 ± 6.8 hours vs 4.7 ± 1.6 hours; P < 0.001), 13 and ultrasound-guided dorsal penile nerve blocks compared with the landmark-based technique (570 [360-860] minutes vs 60 [30-300] minutes; P < 0.0001).…”
Section: B (Us Vs Landmark Method)mentioning
confidence: 89%
See 2 more Smart Citations
“…The duration to first analgesia is significantly higher with ultrasound-guided sciatic and femoral nerve blocks compared with nerve stimulation (8.6 ± 0.66 vs 7.6 ± 0.57 hours; P < 0.001), 9 but there was no difference in infraclavicular brachial plexus blocks when the 2 techniques were compared. 10 Time to first analgesia was longer with ultrasound-guided TAP block compared with no block (14.1 ± 4.9 hours vs 1.3 ± 1.1 hours; P < 0.05), 5 ultrasound-guided TAP block compared with wound infiltration (17 ± 6.8 hours vs 4.7 ± 1.6 hours; P < 0.001), 13 and ultrasound-guided dorsal penile nerve blocks compared with the landmark-based technique (570 [360-860] minutes vs 60 [30-300] minutes; P < 0.0001).…”
Section: B (Us Vs Landmark Method)mentioning
confidence: 89%
“…Success with ultrasound guidance was higher than with nerve stimulation guidance for infraclavicular brachial plexus (96% vs 64%; P = 0.005) 10 and sciatic and femoral nerve (97% vs 76%; P = 0.026) blocks. 9 Elnour et al 4 documented a higher block success in ultrasound guidance compared with nerve stimulation (85% vs 75%) for axillary brachial plexus blocks; however, this difference was not statistically significant (P = 0.43). Furthermore, in a prospective observational study of 45 children undergoing foot surgery, it was shown that the success of ultrasound-guided sciatic nerve blocks did not depend on the ability to elicit a motor response using nerve stimulation.…”
Section: Peripheral Nerve Blocksmentioning
confidence: 95%
See 1 more Smart Citation
“…For instance, USG pediatric axillary block performance was slightly faster compared with PNS (14.6 ± 3.0 vs 16.1 ± 2 minutes, respectively, P = 0.035), 71 but when USG was compared with a landmark-based penile block, performance time was longer by an average of 75 seconds 72 (level Ib evidence). Two new RCTs reported increased block success with US as compared with PNS for infraclavicular 73 and femoral sciatic blocks, 74 but no difference with axillary block 71 (level Ib evidence). When block success was assessed by opioid consumption, there was no difference between US and PNS.…”
Section: Pediatric Blocksmentioning
confidence: 99%
“…Ancak USNS grubunda daha fazla iğne yönlendirmesi gerekmiş ve blok daha geç gerçekleş-miştir [11]. Ponde ve arkadaşları ise 8aylık ile 2yaş arasında artrogripozis multipleks nedeniyle opere olacak çocuklarda USG ve NS kullanımını femoral-siyatik sinir bloğu kullanımında karşılaş-tırmışlar, USG kullanımının blok başarısını arttırdığını ve ilk analjezik kullanım zamanını uzattığını bulmuşlardır [12]. Yakın döneme kadar US eşliğinde perinöral devamlı katater yerleştirme üzerine az sayıda çalışma bulunmaktadır [1,2].…”
Section: Discussionunclassified